2020
DOI: 10.1101/2020.04.27.20081596
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dietary diversity practice and associated factors among pregnant women attending ANC in Kolfe Keranyo sub city health centers, Addis Ababa, Ethiopia

Abstract: Background: Adequate and healthy diet during pregnancy is essential for the health of both mother and newborn. Dietary diversity is a proxy indicator of maternal nutrient adequacy. However, little is documented on dietary diversity among pregnant women. Objectives: This study was designed to assess the dietary diversity practice and associated factors among pregnant women attending ANC in health centers of the coffee keranyo sub city, Addis Ababa, Ethiopia. Methods: Institution based cross-sectional study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
3
9
3
Order By: Relevance
“…This study was aimed to assess the minimum dietary diversity and associated factors among pregnant women attending ANC at Wacha primary hospital, Southwest Ethiopia. According to this study finding around 51% of pregnant women had met a minimum dietary diversity which is lower than the study finding from Burkina Faso (68.4%) [30], Addis Ababa (60.9%) [40], Hosanna town of Ethiopia (75.8%) [41], and Alamata (61.2%) [2]; and while higher than the national level of Ethiopia (47%) [27], SNNPR region of Ethiopia (28%) [23], East Gojjam Zone of Northwest Ethiopia (45%) [42], Jille Tumuga (31.4%) [32], Bale (44.8%) [33], Dire Daw city (43%) [39] and Shashemene town (25.4%) [43]. The possible explanation for this prevalence discrepancy might be due to study periods differences, geographical differences, socio-cultural differences, and differences in the measurement of dietary diversity which some study uses nine food groups and while other studies used the 14 food groups, and those consumed four or more food groups of the fourteen food groups were classified as minimum dietary diversity which will result in a greater score than this finding.…”
Section: Minimum Dietary Diversity Of Pregnant Womencontrasting
confidence: 75%
“…This study was aimed to assess the minimum dietary diversity and associated factors among pregnant women attending ANC at Wacha primary hospital, Southwest Ethiopia. According to this study finding around 51% of pregnant women had met a minimum dietary diversity which is lower than the study finding from Burkina Faso (68.4%) [30], Addis Ababa (60.9%) [40], Hosanna town of Ethiopia (75.8%) [41], and Alamata (61.2%) [2]; and while higher than the national level of Ethiopia (47%) [27], SNNPR region of Ethiopia (28%) [23], East Gojjam Zone of Northwest Ethiopia (45%) [42], Jille Tumuga (31.4%) [32], Bale (44.8%) [33], Dire Daw city (43%) [39] and Shashemene town (25.4%) [43]. The possible explanation for this prevalence discrepancy might be due to study periods differences, geographical differences, socio-cultural differences, and differences in the measurement of dietary diversity which some study uses nine food groups and while other studies used the 14 food groups, and those consumed four or more food groups of the fourteen food groups were classified as minimum dietary diversity which will result in a greater score than this finding.…”
Section: Minimum Dietary Diversity Of Pregnant Womencontrasting
confidence: 75%
“…Of all the included studies, nine studies [ 5 , 7 , 14 , 33 35 , 38 , 40 , 49 ] were community based cross-sectional (CBCS) and the rest; fourteen studies were institution based cross-sectional (IBCS) studies study design. Out of 23 studies, only 12 studies [ 5 , 7 , 14 , 34 36 , 38 , 39 , 42 , 44 , 48 , 49 ] were reported essential associated factors of dietary diversity among pregnant woman in Ethiopia. The sample sizes in each study varies from 104 [ 51 ] to 1393 [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Women who can read and write were 82% more likely to consumed diversified food than who cannot read and write ( Fig 7 ). Seven studies [ 7 , 34 , 35 , 39 , 44 , 48 , 49 ] were assessed the primary school educated with dietary diversity. Of those seven studies, two studies reported the association between primary school educated women with dietary diversity during pregnancy is insignificant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations